Analisis Alokasi Anggaran Dan Prioritas Pembangunan Daerah Di Kabupaten Sarolangun - Lailatul Anip (Jurnal Dinamika Manajemen, 2016)
This thesis is entitled analysis of budget allocations and regional development priorities of Sarolangun Regency in 2007-2012. The aim of this study was to find out the analysis of the priority budget allocation for regional development in Sarolangun Regency, the development of the priority budget for regional development. The method used is descriptive analysis and uses developmental analysis. The results of this study show that the priority budget for regional development is increasing every year, especially for the first priority in 2010 by 47%, in 2011 by 26% and in 2012 by 29%. regional development priorities every year or in the future the number of special regional expenditures for regional development priority budgets will increase.